A ulva lactuca-derived porous carbon for high-performance electrode materials in supercapacitor: Synergistic effect of porous structure and graphitization degree. (January 2021) - Gang, Bojie; Zhang, Feng; Li, Xiuli; Zhai, Bin; Wang, Xiuying; Song, Yu
Highlights: A series of ulva lactuca-derived carbon materials were synthesized. Porous structure and graphitization degree could be controlled. The optimal carbon material exhibited excellent supercapacitor performance. Abstract: Exploitation of biomass derived carbon material with appropriate porous structure and graphitization degree is supposed to be an effective approach for the improvement of supercapacitor. In this work, we synthesized partially graphitic porous carbon materials using ulva lactuca and Ni species as carbon source and catalyst via a "adsorption-pyrolysis-removal" process. Moreover, the porous structure and graphitization degree of the obtained carbon materials could be easily controlled via adjusting the amount and type of Ni-based salts. When these carbon materials were used as electrode materials for supercapacitor, the carbon material demonstrated a specific capacitance of 167 F g − 1 at 1.0 A g − 1 in a two-electrode symmetrical cell, which is higher than that of most reported biomass derived carbon materials. Furthermore, it is found that the influence of porous structure and graphitization degree on the electrochemical performance has the synergistic effect. This work provides a promising approach to fabricate carbon materials with superior electrochemical performance by using ulva lactuca as carbon source. Graphical abstract: Image, graphical abstract